Editorial for Special Issue: “In Situ Data in the Interplay of Remote Sensing” - Mona Morsy; Erik Borg; Peter Dietrich (Remote Sensing, 2023)
The importance of remote sensing in solving challenges in rural and undeveloped areas where there is a lack of in situ data or financial resources is undeniable [...]